The Impact of New Electricity Reform on the Management of Power Network Investment Planning and Its Countermeasures - Cui Kai; Zhao Juan; Wu Xiao; Li Hui; Tian Yanhua; Li Jing (E3S Web of Conferences, 2019)
A new round of power system reform will gradually promote the construction of power market in China. In this process, many policies will have an impact on the investment plan management of power grid enterprises. Firstly, this paper analyses the basic framework of China’s new power reform and two key tasks affecting grid investment. Then, the impact of electricity reform policy on investment decision-making of power grid is analyzed, including investment planning objectives, planning principles, planning depth, planning effectiveness and investment management. Finally, the investment plan management strategy of power grid company under the new situation is put forward.